Jinxed - McCulloch, Amy, 1986- (Jinxed, 2020)
After fourteen-year-old Lacey Chu repairs a highly advanced smartphone/robotic pet companion, or baku, called Jinx, the baku gets her into her dream school, Profectus, where she is exposed to dangerous secrets.